Prevalence of Pain In Depressed Patients and Its Impact on Treatment Outcomes - Awais, Muhammad (Biological and Clinical Sciences Research Journal, 2025)
Depression and pain frequently co-occur, sharing overlapping neurobiological mechanisms that can amplify symptom severity and hinder treatment efficacy. Chronic pain among individuals with depression substantially affects their functional outcomes and quality of life, yet integrated management approaches remain underutilized. This study aimed to determine the prevalence of pain in patients with depression and evaluate its impact on treatment outcomes. Methods: This prospective, randomized controlled trial was conducted over six months at the psychiatric outpatient department of a tertiary-care teaching hospital. A total of 200 adults diagnosed with Major Depressive Disorder or Persistent Depressive Disorder (DSM-V criteria) were enrolled and randomly assigned to either an intervention group receiving structured collaborative care or a control group receiving standard care. Depression severity was assessed using the Hopkins Symptom Checklist-20 (HSCL-20), and pain interference was evaluated through the Short Form-36 (SF-36) pain subscale at baseline, 3 months, and 6 months. Data were analyzed using repeated-measures ANOVA and multivariate regression to identify predictors of depression outcomes. Results: At baseline, 42% of participants reported moderate to severe pain interfering with daily activities. Both groups showed significant improvements in HSCL-20 and SF-36 scores over six months (p < 0.001). The intervention group exhibited greater improvement in depressive symptoms (p = 0.03), while pain reduction was comparable between groups (p = 0.41). Despite overall progress, 32% of patients continued to report moderate pain at 6 months. Regression analysis revealed that baseline pain severity and reduction in pain over time significantly predicted depression remission (p < 0.001). A significant interaction between pain reduction and treatment group was observed (p = 0.027), suggesting that integrated care enhanced depression recovery independent of pain persistence. Conclusion: Pain is highly prevalent among patients with depression and significantly influences treatment outcomes. Although depressive symptoms improved in both study groups, persistent pain remained in a substantial subset, underscoring the need for integrated, multidisciplinary approaches addressing both mood and pain symptoms concurrently. Collaborative care demonstrated superior efficacy in improving depression, supporting its adoption in clinical practice to optimize holistic recovery.